2022
DOI: 10.2106/jbjs.21.01034
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Wider Medial Gap (Medial Laxity) in Flexion with Self-Reported Knee Instability After Medial-Pivot Total Knee Arthroplasty

Abstract: Background:Medial-pivot total knee arthroplasty (TKA) is designed with high articular conformity in the medial compartment in order to achieve stability. The subjective outcome of patients has been reported to be good postoperatively; however, the association between the objective and subjective knee stability and the influence of subjective stability on the overall outcomes of TKA remained unknown. Our hypothesis was that postoperative flexion joint-gap imbalance could affect subjective knee instability follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A key difference of FA over KA and other nMA’s is that FA not only attempts to realign the knee in the coronal plane in extension but also aims to do the same in flexion alignment, which typically receives less attention as it is more challenging to measure flexion alignment pre‐operatively and post‐operatively. Predicting and realigning the knee through its ROM curve allows the soft tissue to maintain appropriate tension, restore normal kinematic features such as medial pivot, and avoid flexion instability [26, 27]. Additionally, FA accepts that a compromise on implant alignment or position may be required to restore suitable kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…A key difference of FA over KA and other nMA’s is that FA not only attempts to realign the knee in the coronal plane in extension but also aims to do the same in flexion alignment, which typically receives less attention as it is more challenging to measure flexion alignment pre‐operatively and post‐operatively. Predicting and realigning the knee through its ROM curve allows the soft tissue to maintain appropriate tension, restore normal kinematic features such as medial pivot, and avoid flexion instability [26, 27]. Additionally, FA accepts that a compromise on implant alignment or position may be required to restore suitable kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…The FJS-12 scale was created in recent years to evaluate the degree of knee joint forgotten, existing studies have found that multiple factors have negative correlations with FJS-12 after surgery, such as preoperative depression, postoperative patellar subluxation [ 41 ] and knee instability [ 42 ]. Recent studies have found that the FJS-12 score of diabetic patients is lower than that of non-diabetic patients 1 year after surgery, and the difference is more obvious in female patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the accuracy of the bone cut is increasing owing to the development of the navigation and robot systems [15], such inter-surgeon diference may have signiicant clinical relevance in robotic-assisted TKAs. Because the medial lexion gap is a reliable indicator of softtissue balancing and is associated with patient satisfaction and patient-reported subjective scores after TKA [1,16,19], manual stress measurements in navigation and robot systems must be improved [4,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate soft-tissue balancing is important in achieving a good clinical outcome, patient satisfaction, and a long-term implant survival after total knee arthroplasty (TKA) [1,3,5,11,19]. Joint gap measurement is most commonly performed under static conditions, with the knee extended and performing a 90° lexion using a gap tensioner/spreader [18].…”
Section: Introductionmentioning
confidence: 99%